Analysis of Utilization of the Nursing Laboratory as a Convenience for Independent Skills Training Basic Nursing Course Students of Baturaja Nursing Study Program in Health Polytechnic Palembang - Lisdahayati; A. Gani (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the description and factors related to the use of the nursing laboratory as a place to train the skills independently of students of the Baturaja Nursing Study Program. Data were collected using a quantitative approach with Chi-Square statistical test. The research activity lasted for 6 (six) months. The results of the research from 78 respondents have mostly used the laboratory as a place to practice independent laboratory practice skills. Suggestions to the Baturaja Nursing Study Program to further increase student participation in terms of activeness in practicing independent skills in nursing laboratories so that students are skilled in carrying out action procedures and have readiness during clinical practice in the field and have confidence when dealing directly with patients, and for teaching lecturers.